1985
DOI: 10.1038/hdy.1985.11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in recombination in Drosophila. II. Genetic analysis of a high recombination stock

Abstract: The difference in Gl-Sb recombination frequency between two stocks of Drosophila melanogaster, H and C, has been analysed genetically. (The H stock was obtained by artificial selection for increased recombination.) Chromosome substitution experiments show that all three major chromosome contain genes which contribute to the H-C difference, and that there are significant interactions between the genes on different chromosomes. In particular, the H 2nd chromosome increases recombination on a background of homozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…However, the observed pattern of recombination changes across the genome does not necessarily reflect directly the distribution of geotaxis or rec-loci. Indeed, in experiments with direct selection for recombination, it has been shown that the response to selection for one specific chromosome• region can result in a spectrum of changes in recom- (Chinnici, 1971;Kidwell, 1972;Charlesworth & Charlesworth, 1985). Based on our data and other evidence (Table 1), it can be generalized that directional selection for any trait for many generations can play an important role in rec-system evolution.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…However, the observed pattern of recombination changes across the genome does not necessarily reflect directly the distribution of geotaxis or rec-loci. Indeed, in experiments with direct selection for recombination, it has been shown that the response to selection for one specific chromosome• region can result in a spectrum of changes in recom- (Chinnici, 1971;Kidwell, 1972;Charlesworth & Charlesworth, 1985). Based on our data and other evidence (Table 1), it can be generalized that directional selection for any trait for many generations can play an important role in rec-system evolution.…”
Section: Resultsmentioning
confidence: 62%
“…The main arguments against such an interpretation and in favour of the one presented here are: (i) the unidirectional mode of changes in if in both geo + and geo (which are more than simply two independent replications); (ii) reaction of different genome regions in the same direction; (iii) very high rates of if-reaction are not very common in experiments with direct selection for recombination. In fact, the observed differences between opposite selection lines rarely exceed the two or threefold level (Chinnici, 1971;Kidwell, 1972;Dewees, 1975;Charlesworth & Charlesworth, 1985; but see Turner, 1979); and (iv) good reproducibility of the effects between replications (eight replications for each line tested for each of the three chromosomes).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is unknown whether changes in recombination among experimental treatments result from direct selection on recombination frequency itself or as an indirect consequence of selection on other traits. Both increases and decreases in recombination rate have been observed in laboratory selection experiments in which recombination rate itself was successfully subjected to artificial selection (Chinnici 1971;Kidwell 1972;Charlesworth and Charlesworth 1985). However, changes in recombination rate have been also shown to evolve as a correlated response to artificial selection on other characters (Flexon and Rodell 1982;Zhuchenko et al 1985;Korol and Iliadi 1994;Rodell et al 2004).…”
Section: Genetic Variation In Recombinationmentioning
confidence: 98%
“…These poly. genes can readily respond to intense directional artificial selection (Shaw, 1972(Shaw, , 1974Charlesworth and Charlesworth, 1985). However, if selection acts with low coefficients-as is probably the case for chiasma frequency adjustment-the response would be improved if there were a major gene or a chromosomal rearrangement that produced a marked effect on chiasma frequency and/or distribution.…”
mentioning
confidence: 99%